THE LOWRIE-FULLER TEST: SINGLE-DOMAIN AND MICROMAGNETIC THEORY - Newell A.J. (My University, 2000)
Lowrie and Fuller [J. Geophys. Res. 76 (1971) 6339-6349] proposed a test to distinguish between single-domain (SD) and multi-domain remanence using alternating field (AF) demagnetization. However, their criterion for SD grains, derived from experiments on nominally SD samples, seems to contradict the SD theory. A new, more general SD theory is presented that includes the effects of variations in grain shape and volume, applied stress and composition. One factor is varied at a time while the others are held fixed. If the variable is stress or grain shape, the AF demagnetization curves do not satisfy the Lowrie-Fuller criterion for SD grains, as noted in earlier work. The same is true for variable composition if the magnetic hysteresis is controlled by shape anisotropy. Grain volume affects the AF demagnetization curve through thermal fluctuations. When the variable is volume, the sample passes the Lowrie-Fuller test. If the variable is grain orientation, the outcome depends on the distribution of orientations and the direction of the field. A highly anisotropic sample will pass the Lowrie-Fuller test in one direction and fail it in another. Thus, depending on the dominant variable, an ensemble of SD grains can pass or fail the Lowrie-Fuller test. However, a full analysis of the Lowrie-Fuller test must also take into account the critical sizes for transition from SD to non-SD properties. In particular, above the critical volume VSDc°erc, the magnetization reverses by non-uniform rotation. In samples that have been used to test the SD theory, the range of volumes is broad and most of the remanence is carried by grains larger than VSDc°erc. The SD theory will only apply to samples with grain volumes concentrated near the superparamagnetic-SD boundary. Such samples will have many characteristics usually attributed to MD grains. The shapes of their AF demagnetization curves will be determined mainly by the volume distribution. Therefore, they will satisfy the Lowrie-Fuller criterion for SD grains.
Keywords: ALTERNATING FIELD DEMAGNETIZATION; REMANENT MAGNETIZATION; THERMOREMANENT MAGNETIZATION; MAGNETIC DOMAINS